Plasmodium chez les grands singes africains - Linda Duval (Revue de Primatologie)
In the early twentieth century, only three species of Plasmodium, P. schwetzi, P. rodhaini and P. reichenowi were known and described in chimpanzees and gorillas in Africa. These studies were based on morphological and biological descriptions of the parasites. With the development of molecular diagnostic tools and their use on a larger scale the knowledge in the field of Plasmodium in African apes has increased significantly. Thus, a large molecular diversity of Plasmodium infecting chimpanzees, gorillas and bonobos in Africa was recently discovered. Several research teams have participated in these major advances. This papers aims to give an update on these results and on the knowledge gained in recent years in this area.